Fabella Syndrome: Anatomy, Diagnosis, Treatment, and Outcomes - Mason Nolan; Ethan Marting; James Applegate; Conor Wood; Sarah Willard; Morgan Turnow; Benjamin C. Taylor (Anatomia)
The fabella is a rare sesamoid bone found within the posterior aspect of the knee joint. Patients can suffer from fabella syndrome which is characterized as pain with extension of the knee, ultimately limiting motion and causing a clicking or catching sensation. There is debate in the literature regarding operative excision versus nonoperative management for patients with fabella syndrome. This review seeks to provide a comprehensive overview of fabella anatomy and fabella syndrome presentation, diagnosis, treatment, and outcomes.